PENCEGAHAN PENYAKIT MENULAR TUBERCULOSIS DENGAN METODE SIMULASI SNAKES & LEDDER TUBERCULOSIS PADA REMAJA - Ferawati; Fitria Rizki; Zainal Abidin, Ahmad; Anugerah Hadi Sulistyo, Angger (LPPM ISTeK ICsada Bojonegoro, 2024)
Sumberejo Village, which is included in the Trucuk District area, has 10 RTs. In Sumberejo Village, the program to prevent infectious diseases, especially TB, has not been running well for village teenagers. Based on information from health cadres, this program is not yet optimal in this village, apart from the fact that the distance is too far between residence and location, because the quality of knowledge, behavioral attitudes and health environment among teenagers is still lacking. This can trigger teenagers' ignorance about infectious diseases. The most common infectious disease currently occurring is tuberculosis. Adolescents must have action in terms of knowledge, causes, prevention and at least know how to deal with it, so that they have adequate capacity to respond to problems that occur in the surrounding environment. There are several methods commonly used to prevent disease transmission, including optimizing education using different media, namely snake & ledeers simulations. This activity was carried out in 10 families in Sumberejo Village. This activity was carried out over 6 meetings or visits, starting with an assessment, creating a PoA, preparing interventions and carrying out implementation and evaluation. Sumberejo Village, which is included in the Trucuk District area, has 10 RTs. In Sumberejo Village, the program to prevent infectious diseases, especially TB, has not been running well for village teenagers. Based on information from health cadres, this program is not yet optimal in this village, apart from the fact that the distance is too far between residence and location, because the quality of knowledge, behavioral attitudes and health environment among teenagers is still lacking. This can trigger teenagers' ignorance about infectious diseases